2017
DOI: 10.1080/21645515.2017.1356521
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of recombinant adenovirus expressing a fusion gene from GM-CSF and Epstein-Barr virus LMP2A in a mouse tumor model

Abstract: In this study, purified GM-CSF and LMP2A mRNAs were amplified by PCR. Then, the GM-CSF and LMP2A sequences were connected by the polypeptide linker (GlySer) using gene splicing by overlap extension. The constructed fusion gene GC2A was inserted into the adenovirus vector. Then the recombinant vector was introduced into HEK 293T cells by calcium phosphate transfection to package the adenovirus. The levels of antibodies against the GM-CSF and LMP2Afusion proteins were measured by ELISA, and the CTL activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Cyclophosphamide (CP), an immunosuppressant, was simultaneously delivered by the PD1-expressing platelets to exhaust the regulatory T cells (Tregs) and enhance the cytotoxic effects of the CD8 + T cells. Xue et al conjugated granulocyte macrophage-colony stimulating factor (GM-CSF) mRNAs to polypeptide linker covalently to construct fusion gene GC2A, which was further inserted into the adenovirus vector to transfect human embryonic kidney 293T (HEK293T) cells 109. The recombinant adenovirus proliferated in HEK293T cells and released GM-SCF that promoted the DC proliferation and differentiation in the tumor-bearing mice.…”
Section: Engineering Cells Via Genetic Modificationmentioning
confidence: 99%
“…Cyclophosphamide (CP), an immunosuppressant, was simultaneously delivered by the PD1-expressing platelets to exhaust the regulatory T cells (Tregs) and enhance the cytotoxic effects of the CD8 + T cells. Xue et al conjugated granulocyte macrophage-colony stimulating factor (GM-CSF) mRNAs to polypeptide linker covalently to construct fusion gene GC2A, which was further inserted into the adenovirus vector to transfect human embryonic kidney 293T (HEK293T) cells 109. The recombinant adenovirus proliferated in HEK293T cells and released GM-SCF that promoted the DC proliferation and differentiation in the tumor-bearing mice.…”
Section: Engineering Cells Via Genetic Modificationmentioning
confidence: 99%
“…The results of this study showed that BCG and pMV261 + BCG could inhibit EBV-positive tumor cells at an early stage, which may be related to the ability of BCG to activate cellular immunity and, to some extent, kill tumor cells. 20 At the later stage of tumor growth, only the rBCG group exerted obvious inhibitory effects on tumor cells. At the same time, the results also suggested that BCG and BCG+ pMV261 alone can inhibit the division and growth of tumor cells through nonspecific immune responses at an early tumor stage.…”
Section: Discussionmentioning
confidence: 98%
“…RT-PCR was used to clone the hGM-CSF and LMP2A cDNAs, and a polypeptide linker (Gly 4 Ser) 3 was used to construct the fusion genes. 20 Specific primers were designed for LMP2A, hGM-CSF and the fusion gene according to the open reading frame sequences of LMP2A and hGM-CSF.…”
Section: Methodsmentioning
confidence: 99%
“…In the past ten years, the research direction of oncolytic adenovirus has evolved from the use of genes to maximize the immediate killing of tumor cells to amplify the immune response induced by viral oncolysis. Inspired by this concept, more oncolytic adenoviral vectors are loaded with immunomodulatory factors, including GM-CSF, CD40 ligands, or interferon-1 (IFN-1) [ 53 ].…”
Section: Types and Characteristics Of Ovsmentioning
confidence: 99%